A arte civil de Mestre Valentin: um programa de sombra e de água fresca - Carvalho, Anna Maria Fausto Monteiro de (1988)
Relate the Bhazilian artistic process of the colonial period to the practices applied by the absolutist Portuguese se state to enforce its domination on the colonial society's production system. The city of Rio de Janeiro in the XVIII century is emphasized inasmuch as it became the viceroyal Government's site. Within that city it is focused the civil works os Mestre Valentin, the generator of new dimensions in the Brazilian visual arts. The analysis is carried out through critical research of the History of Art, a study open to interdisciplinarity, approximating the concept of production relations of the artistic evente, proposed by Damisch, Duvignaud and Panofsky, within the notion of discontinuous time contained in the thinking of Braudel, Deleuze, Foucault and Nietzsche.